2008
DOI: 10.1094/mpmi-21-2-0269
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. tomato DC3000 Uses Constitutive and Apoplast-Induced Nutrient Assimilation Pathways to Catabolize Nutrients That Are Abundant in the Tomato Apoplast

Abstract: The plant apoplast is the intercellular space that surrounds plant cells, in which metabolic and physiological processes relating to cell wall biosynthesis, nutrient transport, and stress responses occur. The apoplast is also the primary site of infection for hemibiotrophic pathogens such as P. syringae, which obtain nutrients directly from apoplastic fluid. We have used apoplastic fluid extracted from healthy tomato leaves as a growth medium for Pseudomonas spp. in order to investigate the role of apoplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
220
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(255 citation statements)
references
References 88 publications
21
220
2
2
Order By: Relevance
“…Since neem extract could not induce lysozyme activity when applied in combination with the pathogen, it can be hypothesized that the pathogen effector proteins probably interfere with the elicitation properties of the bioelicitor. This appears to be in agreement to the findings of Rico and Preston (2008), who reported that such effector proteins can potentially inactivate plant surveillance mechanisms and signaling pathways, thus allowing the survival of the pathogen on the leaf surface. Hauck et al (2003) demonstrated that AvrPto, an effector molecule of P. syringae pv.…”
Section: Discussionsupporting
confidence: 92%
“…Since neem extract could not induce lysozyme activity when applied in combination with the pathogen, it can be hypothesized that the pathogen effector proteins probably interfere with the elicitation properties of the bioelicitor. This appears to be in agreement to the findings of Rico and Preston (2008), who reported that such effector proteins can potentially inactivate plant surveillance mechanisms and signaling pathways, thus allowing the survival of the pathogen on the leaf surface. Hauck et al (2003) demonstrated that AvrPto, an effector molecule of P. syringae pv.…”
Section: Discussionsupporting
confidence: 92%
“…actinidiae chemoreceptors [75] and a modified phenoarray approach was applied to analyze the apoplast-adapted nutrient assimilation pathways of P. syringae pv. tomato DC3000 [76]. Although it has not been definitely confirmed that the 8-HQ efflux in Psn23 is mediated directly by the transporter encoded by the matE gene, the PM technology approach used herein demonstrated that the impact caused by TTTS and IAA metabolism on the P. savastanoi fitness goes beyond its pathogenicity and virulence and also involves drug and antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 77%
“…Previous metabolomic studies of cell wall fractions of French bean and Arabidopsis cell wall cultures re- (Bolwell, 1999;Bolwell et al, 2002). Organic acids have also been found in P. syringaeinfected plants (Rico and Preston, 2008).…”
Section: Knockdown Of Prx33/prx34 Leads To a Differential Accumulatiomentioning
confidence: 93%